China’s approach to malaria control and elimination: Adaptive management and policy capacity building - Wei Ding; Duoquan Wang; Shenning Lu; Xiao-Nong Zhou; Lewis Husain (Global Public Health)
Malaria remains a major global public health burden and is a potential priority for Chinese health cooperation. However, limited analysis exists on the reference value of China’s malaria elimination experience for other countries. While existing studies have focused on specific control strategies used in China, few have examined how Chinese malaria policy and practice have been adapted over time in response to heterogeneity across a vast country. This paper draws on literature, policy reviews, and in-depth interviews with key informants, including government officials and experts involved in malaria policy or implementation. It analyses the evolution of Chinese malaria policy from the 1950s to 2020 and presents case studies profiling specific practices through the lenses of policy experimentation and ‘policy capacity’. The findings highlight how adaptive malaria policy and practice in China responded not only to the changing distribution and burden of malaria but also to shifts in institutions and the political economy as the country developed. Experimentation facilitated adaptive, sequential problem-solving, starting from a low base with limited data availability and capacity. China’s experience offered valuable insights for other countries and for the evolution of its health cooperation initiatives.